Oral submucous fibrosis: Current concepts on aetiology and management - A review - Sadiya Khan; Abhishek Sinha; Shiva Kumar; Haider Iqbal (Wolters Kluwer Medknow Publications, 2018)
Oral submucous fibrosis (OSF) is the chronic debilitating and crippling condition of oral mucosa. It is well recognised as potentially malignant disorder which is associated mainly with the use of arecanut in various forms. It is characterised by inflammation and progressive fibrosis of the submucosal tissue. The pathogenesis of the disease includes various factors like arecanut chewing, chillies, nutritional deficiencies and genetic processes. The management of OSF has been the subject of controversy ever since Schwartz first described the condition in 1952. Through this article, an attempt is made to update the knowledge regarding aetiology and its therapeutic and surgical management which improves the life expectancy of patients suffering from OSF.